PENDEKATAN PERENCANAAN STRATEGIS DALAM PERENCANAAN TATA RUANG KOTA UNTUK PERUBAHAN IKLIM - Ruth Roselin Erniwaty Nainggolan (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2024)
Greenhouse gases, which consist of 55% carbon, have been reported as the most significant contributor to climate change. Greenhouse gases have encouraged various international efforts to reduce carbon levels worldwide. One is emphasizing climate change adaptation and mitigation programs in city development. Planning is an essential element for any urban development initiative. Planning requires making choices in pursuit of stated goals. Understanding urban planning related to climate change as a "wicked problem" is the basis for choosing an appropriate planning approach. Strategic spatial planning is widely practiced worldwide to develop a coordinated vision to guide urban areas' medium to long-term development. However, the literature needs a more comprehensive conceptualization of spatial strategic planning. City spatial strategic planning is primarily published in empirical studies, which generally focus on one case. This article, apart from providing a specific overview of how the strategic planning process is carried out in urban spatial planning related to climate change, also explains various reasons why strategic planning is an appropriate approach in urban planning related to climate change. Keywords : strategic planning, climate change, wicked problem